"The Host of Vagabonds": Origins and Destinations of the Vagrant in Cape History and Ideas - Anderson_PR (Department of English Language and Literature, 2024)
South African history in the crisis of the early 19th century, and South African literature ever since then, have been preoccupied with the vagrant in much the same manner and degree as was the European Renaissance. The subject of this thesis is the history and culture of vagrancy, and specifically the trajectory by which the Renaissance idea of the vagrant becomes transposed to the indigenous population of the colonial Cape and works itself out in literary and historical texts of that society and its successors. It has as its central thesis the claim that a history of the vagrant is not properly to be sought in social and economic realities, but first in the cultural (and here especially textual and literary) forms of the idea by which the vagrant is brought into being. In advancing an apprehension of vagrancy as the ideological accusation of hegemonic order, this thesis argues that the vagrant figures in ideology as the inordinate, and in so doing becomes metonymic for inordinate historical passages - especially revolution and the frontier, moments of rupture and narrative loss, or moments where history'S character of mutability reaches its extreme. Above all, the vagrant represents the inordinate event of history itsel~ and exemplifies the necessity of a scholarship in which historicist literary criticism and textual analyses of history are conjoined Renaissance representations of the vagrant are forged in the nexus of feudal dissolution and capitalist emergence, and themselves belong to a rapidly developing culture and economy of textual commodification. There exists a marked correspondence between these representations and the development of colonial representations of the indigenous 'other', a correspondence by which the colonised is anticipated as a vagrant and thus cast as an extension of the disorderly lumpenproletariat from which imperial capitalism most profitably, and with state sanction, recruits its labour. The first half of this thesis traces exemplary instances of the transfer of vagrant attributes to the colonial subject, and then looks to the ma.nner in which, especially between 1828 and 1834, the idea of vagrancy comes to dominate cultural and political delineation in the Cape. From the Renaissance schedules of Hannan, Awdeley and others, through the canonical accomplishments of King uar, to texts of the historical record in the Cape, and the doggerel squib of A G. Bain's 'Kaatje Kekkelbek', the vagrant is pursued into the more explicitly literary occasions of the thesis's latter half. Here we find the vagrant atthe centre of Fugard and Coetzee, major authors preoccupied with history and indebted to it. A consideration of the vagrant's persistence at the core of 20th century South Mrican literature offers insights into the 'destination' of the vagrant idea, which is to say, just what the depth of the practice of that idea may be, and why - and the thesis concludes by discovering the particular correspondence between vagrancy and history itself.